METAL DEPOSIT OF SLUGS AND PLATES OF CRYSTALLIZERS - A. V. Demin; S. M. Borshchev; V. A. Nikolaev; I. V. Gorevoj (Литьë и металлургия)
The new technology of double protective galvanic coat was developed on the basis of investigations of protective coats of muffs and crystallizers plates for sorted and bloom MNLZ and applying of this coat on muffs and crystallizers plates in conditions of RUP “BMZ'' was assimilated.